MATURITY AND SPAWNING OF THE ANCHOVY, THRISSINA BAELAMA (FORSKAL) FROM THE ANDAMAN SEA - Marichamy, R (Indian Journal of Fisheries, 2011)
The occurrence of mature and spent specimens of Thrissina baelama in different size groups indicated that the fish matures at an average length of 117 nun (TL). This is supported by the results obtained from the study of ponderal index. While the immature females showed a more or less direct relationship between ’Kn’ values and feeding activity, the mature females showed some deviations during certain months. The study of ova diameters has shown that the species spawns twice in a year. Spawning appears to be of short duration and the whole stock of mature ova measuring 0,57-0.84 nun in diameter are extruded during the spawning. Two spawning seasons in a year were observed and these coincided with the two monsoons, during July-August and late November-January. Fecundity ranged between 1171 and 3356 ova in a fish size range of 110-127mm. Logarithmic regressions described the relationship between fecundity and weight of fish and fecundity and weight of ovary.